LEATHER JACKET UMKM WEBSITE DESIGN AND IMPLEMTATION TO SUPPORT PROMOTION INCREASE - Hendro Nugroho; Suparjo Suparjo; Chrisna A Dewi; Linda A Lestari; Andy Rachman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
There are quite a lot of Micro, Small and Medium Enterprises (UMKM) in Sidoarjo, especially in the Candi and Tanggulangin areas. UMKM in the Candi area mainly have the type of leather jacket MSME business. The leather jacket business in Candi sub-district needs assistance to increase the business. The problem faced by UMKM in leather jackets is the promotion of the products they have made. During the COVID-19 pandemic, the leather jacket business experienced difficulties in sales promotions because consumers did not know about these local products. The form of assistance carried out to increase promotion is the creation of websites and blogs that will be easily accessible to all consumers. In making the design and implementation of the website using the Systems Development Life Cyscle (SDLC) model. The process is carried out with the stages of (1) planning, (2) Analysis, (3) Design, and (4) Implementation. The results obtained in making a website as a promotional medium can increase consumer interest in buying the desired leather jacket product.